Dynamic sales tax competition: Evidence from panel data at the border - Melissa Gentry; Nadia Greenhalgh-Stanley; Shawn M. Rohlin; Jeffrey P. Thompson (Federal Reserve Bank of Boston, 2020)
We examine both vertical and horizontal tax competition over time by studying the strategic response of county sales taxation to state sales taxes and to cross-border neighboring municipalities' combined (state and county) taxes. Using county and state sales tax data from 2003 through 2009, we employ both static and dynamic panel analysis as well as an instrumental variables approach in combination with a border analysis. Our results confirm the presence of tax competition in the cross section, as previous studies have found. Results from the fixedeffects and dynamic panel analysis also indicate the presence of vertical competition, though quite small, as counties are consistently responsive to changes in their own state sales tax level across all models and specifications. However, the panel findings suggest little to no horizontal tax competition. Following Parchet (2019), we address additional concerns about endogeneity by instrumenting the neighboring-county sales tax rate with the state-level sales tax rate of the neighboring state. Results from instrumental variables analysis reinforce the presence of a small vertical tax competition between local and state sales tax policies. Interestingly, our results, like those of Parchet (2019), indicate that cross-border local sales tax rates act as strategic substitutes.
Keywords: H2; H7; 330; tax competition; sales taxation; border approach